Capabilities of simple calculation models for the analysis of power reactors - Mohamed A. Gaheen (Nuclear Engineering and Technology, 2025)
A simple model was developed for the calculation of the coupled kinetics and thermal-hydraulics response of power reactor cores. The developed model was used for the analysis of the Special Power Excursion Reactor Test III (SPERT-III) E-Core and Loss of Fluid Test (LOFT) Experiment L9-3. The model prediction results were compared with the experimental data for the reactivity insertion and loss of secondary feed water transients without scram. The comparison showed that the model predictions are accurate enough to confirm the capabilities and adequacy of the model. It can be concluded that the model results provide confidence in the application of simple calculation models to the analysis of power transients.